Astronomy and planetology - Apfel, Necia H. (Projects for young scientists., 1983)
Gives instructions for building or making theodolites, sundials, telescopes, spectroscopes, planetariums, and models of stars, and describes methods and times for observing the sun, moon, planets, stars, comets, and meteors.